Prevalence and associated risk factors of reproductive morbidity in Gujarat: evidences from National family health survey-IV - Desai, Gayatri S.; Ghosh, Koustav; Pandya, Sunita V. (International Journal Of Community Medicine And Public Health, 2022)
Background: Every year 50 million women are affected by maternal morbidity and for at least 18 million of them these morbidities become long-term and are often debilitating. To reduce the maternal mortality ratio, as per the target 3.1 of Sustainable Development Goals (SDGs), India needs to continue strengthening its efforts for improving maternal health. The study aims to find out the prevalence and associated risk factors of reproductive morbidity in Gujarat. Methods: The present study has utilised National family health survey-4 (2015-16) data. The survey provides information related to reproductive morbidity including maternal morbidity. Bivariate analysis with Chi-square test and logistic regression has been utilised to show the prevalence and risk factors of reproductive morbidity in Gujarat. Results: Prevalence of reproductive morbidity during pregnancy is 58.1 percent. The morbidity was the highest during delivery (39.44%) and lowest in post-delivery period (12.97%). Looking to the risk factors, education, women’s autonomy and experience of IPV were found to be significant predictors of such a morbidity. Conclusions: Targeted measures directed to check violence against women can help in reducing reproductive morbidities among women in Gujarat. This can ultimately lead to reduction in maternal mortality level as targeted under SDG.